Model Jigsaw dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS di Kelas 6 SDN Citamiang 1 Kecamatan Citamiang Kota Sukabumi - Agnes Kusumahandari (utile: Jurnal Kependidikan, 2018)
The research using cooperative model of jigsaw technique is implemented to raise an IPS learning phenomenon in class which is predicted to increase the attention, courage, and student's sincerity so that students become active and creative. This research uses qualitative method with observation technique and quantitative method with technique counting the final score of students on pascates. The number of students studied as many as 32 students of grade 6, including the steps of research, planning, implementation (action), observation and reflection with 2 cycles. The results showed that: 1) In general, students 'attention increased during KBM, 2) The students' courage to appear to answer the teacher questions in cycle I was little but continued to increase in cycle II after receiving repeated explanation from teacher; 3) At first the students' answers are less than perfect and there are many mistakes in cycle I, 4) In cycle II only a few students ask questions, but then increase in cycle II after the teacher convince students not to fear wrong; 5) Ability and carefulness of students to avoid similar mistakes for tasks that the level of difficulty is almost the same, 6) In the first cycle, attention, way, sincerity and ability of students accomplish light tasks is very less, but then increased after teachers continuously monitor the entire group on cycle II; 7) In cycle I the attention, manner, seriousness and ability of the students to complete the heavy tasks are few, but the students' ability increases in cycle II after the teacher helps to lead to each group; 8) the number of students who ask questions, responses, comments, suggestions, criticisms is minimal in cycle I and only then increases in cycle II after teachers can convince students not to hesitate to ask questions, responses, comments, criticisms; 9) The number of students who got the first grade in cycle I was only 18 people (64.22%) and increased to 29 people (90%) in cycle II, there was an increase of 60.89; 10) The number of students who have decreased the value or the value remains in the first cycle of 3 people and in cycle II there is no impairment.